Glucose transport via the pseudomonad porin OprB: implications for the design of Trojan Horse anti-infectives. Issue 16 (5th April 2019) - Coines, Joan; Acosta-Gutierrez, Silvia; Bodrenko, Igor; Rovira, Carme; Ceccarelli, Matteo
Abstract : Knowing the structural and dynamical features of specific porins from poor-permeable Gram-negative bacteria helps to design anti-infectives with optimal permeation. Molecular dynamics simulations can characterize and quantify the transport of substrates through these specific porins. Abstract : Deciphering the transport through outer-membrane porins is crucial to understand how anti-infectives enter Gram-negative bacteria and perform their function. Here we elucidated the transport mechanism of substrates through the Pseudomonads sugar-specific porin OprB by means of multiscale modeling. We used molecular dynamics simulations to quantify the energetics of transport and thus a diffusion model to quantify the macroscopic flux of molecules through OprB. Our results show that Trp171 and several glutamate residues in the constriction region are key for the transport of glucose, the preferred natural substrate, through OprB. The unveiled transport mechanism suggests that 2-acetamido-1, 2-dideoxynojirimycin (DNJ-NAc), an anti-infective structurally similar to glucose, can enter the cell via OprB. We quantified its energetics and macroscopic flux through OprB providing a comparative analysis with the natural substrate. Thus this pore can be considered as a promising gateway for exploiting the Trojan Horse strategy in pathogenic bacteria.